Development of causal interactions between systolic blood pressure and inter-beat intervals in adolescents - Svačinová, J; Javorka, M; Nováková, Z; Závodná, E; Czippelová, B; Honzíková, N (Physiological research, 2015)
Systolic blood pressure (SBP) changes control the cardiac inter-beat intervals (IBI) duration via baroreflex. Conversely, SBP is influenced by IBI via non-baroreflex mechanisms. Both causal pathways (feedback - baroreflex and feedforward - non-baroreflex) form a closed loop of the SBP - IBI interaction. The aim of this study was to assess the age-related changes in the IBI - SBP interaction. We have non-invasively recorded resting beat-to-beat SBP and IBI in 335 healthy subjects of different age, ranging from 11 to 23 years. Using a linear autoregressive bivariate model we obtained gain (Gain(SBP,IBI), used traditionally as baroreflex sensitivity) and coherence (Coh(SBP,IBI)) of the SBP-IBI interaction and causal gain and coherence in baroreflex (Gain(SBP->IBI), Coh(SBP->IBI) and coherence in non-baroreflex (Coh(IBI->SBP)) directions separately. A non-linear approach was used for causal coupling indices evaluation (C(SBP->IBI), C(IBI->SBP)) quantifying the amount of information transferred between signals. We performed a correlation to age analysis of all measures. Coh(IBI->SBP) and C(IBI->SBP) were higher than Coh(SBP->IBI) and C(SBP->IBI), respectively. Gain(SBP,IBI) increased and Coh(SBP->IBI) decreased with age. The coupling indices did not correlate with age. We conclude that the feedforward influence dominated at rest. The increase of Gain(SBP,IBI) with age was not found in the closed loop model. A decrease of Coh(SBP->IBI) could be related to a change in the cardiovascular control system complexity during maturation.
Keywords: Heart; Baroreflex; Female; systola; dítě; Adolescent Development; mladý dospělý; ženské pohlaví; Adolescent; srdce; lidé; krevní tlak; vývoj mladistvých; Male; Young Adult; Systole; Child; baroreflex; mužské pohlaví; Blood Pressure; mladiství; Humans